2021
DOI: 10.3389/fphys.2021.693733
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anthropometric, Cardiorespiratory, and Haematological Determinants of Marathon Performance

Abstract: AimWe aimed to investigate the main anthropometric, cardiorespiratory and haematological factors that can determine marathon race performance in marathon runners.MethodsForty-five marathon runners (36 males, age: 42 ± 10 years) were examined during the training period for a marathon race. Assessment of training characteristics, anthropometric measurements, including height, body weight (n = 45) and body fat percentage (BF%) (n = 33), echocardiographic study (n = 45), cardiopulmonary exercise testing using trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For ultra-marathoners, BMI explained about 10 to 12% of the variance in running speed ( Hoffman, 2008 ). In addition, BMI was related to training behaviors for performance prediction in different race distances (e.g., 5 km, 10 km, half-marathon, marathon) ( Christou et al, 2021 ; Thuany et al, 2022b ). BMI was also related to running-related injuries ( Buist and Bredeweg, 2011 ), and needs to be carefully considered in association with training behaviors and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…For ultra-marathoners, BMI explained about 10 to 12% of the variance in running speed ( Hoffman, 2008 ). In addition, BMI was related to training behaviors for performance prediction in different race distances (e.g., 5 km, 10 km, half-marathon, marathon) ( Christou et al, 2021 ; Thuany et al, 2022b ). BMI was also related to running-related injuries ( Buist and Bredeweg, 2011 ), and needs to be carefully considered in association with training behaviors and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (Ultima Series, Medgraphics, Saint Paul, MN, USA) was used for the measurement of maximum oxygen uptake (VO 2max ) during exercise and tidal volume as previously described [26].…”
Section: Exercise Testingmentioning
confidence: 99%
“…Furthermore, this study concluded that higher accumulations of body fat, concentrated in the lower limbs and abdominal region, may have a negative impact on athletes’ performance in this type of event. Lower levels of body fat (≤12%) appear to provide advantages for a faster race [ 11 ].…”
Section: Introductionmentioning
confidence: 99%